Cost-effectiveness analysis of benmelstobart and anlotinib plus chemotherapy versus standard chemotherapy in first-line treatment for extensive-stage small cell lung cancer: Perspectives from the United States and China - Wenwang Lang; Jiangbo Wang; Ming Ouyang; Haiqing Zhao; Tingting Zhou; Lingyue Huang (PLoS ONE, 2025)
Background Benmelstobart combined with anlotinib and chemotherapy has demonstrated significant clinical advantages in extending progression-free survival and overall survival compared to chemotherapy alone in patients with extensive-stage small-cell lung cancer (ES-SCLC). This is the first study to assess its cost-effectiveness from both the US payer and Chinese healthcare system perspectives. Method A Markov state-transition model was utilized for the economic evaluation, reflecting both the perspectives of the US payer and the Chinese healthcare system. Baseline patient demographics and vital clinical data were obtained from the ETER701 trial. Costs and utilities were obtained from open-access databases and published literature. The primary outcomes evaluated were quality-adjusted life years (QALYs), incremental cost-effectiveness ratio (ICER), incremental net health benefit (INHB), and incremental net monetary benefit (INMB). The uncertainties of the model were addressed through probabilistic sensitivity analysis, one-way sensitivity analysis, and scenario analysis. Results In the base-case scenario, adding benmelstobart and anlotinib to chemotherapy increased QALYs by 0.34 at an additional cost of $24,684.07, yielding an ICER of $71,559.84 per QALY. This exceeds the willingness-to-pay (WTP) threshold of $38,042.49 per QALY in China, making the treatment marginally cost-effective, with an INHB of −0.30 QALYs and an INMB of -$11,561.58. In the US, the treatment resulted in a QALY increase of 0.36, but incurred an additional cost of $151,052.04, leading to an ICER of $416,398.56 per QALY, surpassing the US WTP threshold of $150,000. 00. Conclusion The combination of benmelstobart and anlotinib with chemotherapy is not a cost-effective first-line treatment option for ES-SCLC in either China or the US.